Reconsidering postgraduate ‘supervision’ from a participatory action learning and action research approach - Wood, L.; Louw, I. (South African Journal of Higher Education, 2020)
Postgraduate supervision is most often perceived as a one-to-one relationship between an expert and a novice researcher. Even when working in groups, an instructional approach tends to dominate, where the supervisor(s) prescribe(s) the content and process, with a narrow focus on the outcome of degree completion, rather than a more holistic approach to the development of postgraduate scholars. At a time when curriculum transformation is high on the agenda of Higher Education, we problematise this traditional conceptualisation of postgraduate supervision and argue for a more participatory action learning and action research (PALAR) approach to postgraduate learning and development. PALAR creates a relational and reflective space for dialogical conversations, equalizing traditional power relations and democratising knowledge creation. This opens up the possibility for postgraduate candidates to perceive themselves as self-directed lifelong learners and collaborative action leaders, rather than just ‘students’. Using a case example of a postgraduate PALAR retreat, we thematically analyse the data generated from participant reflections, presented over three days in visual, oral and other creative forms. Findings reveal that this approach to postgraduate learning and development enhances critical thinking and promotes collaboration rather than competition. Participants are thus able to see themselves as developing scholars and action leaders within their specific fields of influence. Such outcomes are likely to provide a solid foundation for developing future academics or other professionals, able to model a holistic, participatory approach to knowledge creation in their own practice.